Judicial Transparency - Coteño Muñoz, Alejandro (EUNOMÍA. Revista en Cultura de la Legalidad, 2019)
Judicial transparency represents one of the most important demands from the citizenship to Justice. From the institutions, as well as from Jurisprudence and Doctrine, the importance of this transparency has been repeatedly declared, however, until now, a deep and systematic study of it has not been carried out. That is why this text tries to delve into the concept of “judicial transparency” and set the terms for future studies and reforms. Thus, on the one hand, active transparency is analyzed −the publishing of information− and, on the other hand, passive transparency −the right of access to information−, all this distinguishing between information related to the General Council of the Judiciary or judicial information strictly talking. To end up, conclusions, which defend the need of reforms that broaden judicial transparency, so as not to leave it in simple words, are provided.